2003
DOI: 10.1007/s00253-003-1232-8
|View full text |Cite
|
Sign up to set email alerts
|

Medium and copy number effects on the secretion of human proinsulin in Escherichia coli using the universal stress promoters uspA and uspB

Abstract: The use of the uspA and uspB promoters (universal stress promoters) for heterologous protein production in Escherichia coli is described. Best results were obtained with a moderate copy number vector (15-60 copies) bearing the uspA promoter, reaching 4.6 mg/g dry cell weight (DCW) of ZZ-proinsulin secreted to the periplasm and 1.9 mg/g DCW secreted to the culture medium. These values are about 1.7-fold higher than those previously reported with the same ZZ fusion tag and the SpA leader peptide showing that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Escherichia coli transformed with plasmids with different copy numbers exhibited altered export of human proinsulin to the periplasm (Mergulhao et al, 2003). It was found that the use of plasmids of moderate copy number (15 -60) vs. low (10) copy number increased export, but this study did not include a high copy number plasmid.…”
Section: Discussionmentioning
confidence: 97%
“…Escherichia coli transformed with plasmids with different copy numbers exhibited altered export of human proinsulin to the periplasm (Mergulhao et al, 2003). It was found that the use of plasmids of moderate copy number (15 -60) vs. low (10) copy number increased export, but this study did not include a high copy number plasmid.…”
Section: Discussionmentioning
confidence: 97%
“…coli to overproduce these bacteriocins. This can be explained by many factors, including the structural features of the recombinant gene sequences, the stability and translational efficiency of the mRNA, incomplete processing of signal sequences, the metabolic burden on the host strain, the capacity of the transport system and the potential toxicity of the bacteriocin 14, 3638 . Thus, a low copy vector was the most suitable condition for evaluating the expression of both bacteriocins.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli cells were grown at 37°C in Luria-Bertani (LB) medium (0.5% yeast extract, 1% tryptone, and 0.5% NaCl, pH 7.0). Since complex media such as LB can produce negative effects on the expression of recombinant proteins (Mergulhao et al, 2003), the recombinant E. coli were cultured in M9 medium supplemented with 0.1% glucose, 0.05% yeast extract, 0.05% tryptone, and 100 µg/ml ampicillin at 22°C or 37°C. Induction of each recombinant protein was facilitated by the addition of 0.5 mM isopropyl-β-D-thiogalactopyranoside (IPTG) when the optical density at 600 nm (A600) reached 0.4.…”
Section: Al 2006)mentioning
confidence: 99%